2014
DOI: 10.1080/2159676x.2014.936030
|View full text |Cite
|
Sign up to set email alerts
|

Leading for gold: social identity leadership processes at the London 2012 Olympic Games

Abstract: This paper adopted a social identity approach to explore the media data of leadership

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 41 publications
4
35
0
Order By: Relevance
“…For example, leaders who embody a group's identity are more likely to be supported (van Dijke & De Cremer, 2010), trusted (Giessner & van Knippenberg, 2008), and perceived as effective (van Knippenberg & van Knippenberg, 2005). At the London 2012 Olympic Games successful leaders were more likely to articulate their team's identity, values, and vision in their media communication which may have served to enhance the 'specialness' associated with belonging to the team, and mobilize athletes to performance excellence (Slater, Barker, Coffee, & Jones, 2015). Thus, social identity leadership increases perceived leadership effectiveness, whilst leaders work to proactively advance group identities by articulating shared values.…”
Section: The Social Identity Approach To Leadershipmentioning
confidence: 99%
“…For example, leaders who embody a group's identity are more likely to be supported (van Dijke & De Cremer, 2010), trusted (Giessner & van Knippenberg, 2008), and perceived as effective (van Knippenberg & van Knippenberg, 2005). At the London 2012 Olympic Games successful leaders were more likely to articulate their team's identity, values, and vision in their media communication which may have served to enhance the 'specialness' associated with belonging to the team, and mobilize athletes to performance excellence (Slater, Barker, Coffee, & Jones, 2015). Thus, social identity leadership increases perceived leadership effectiveness, whilst leaders work to proactively advance group identities by articulating shared values.…”
Section: The Social Identity Approach To Leadershipmentioning
confidence: 99%
“…It is then on this basis that leaders exert influence over other group members. In short, this is because it is only when leaders are seen as embodying 'who we are' and 'what we want to be' that their leadership engenders followership [125,111,149,150].…”
Section: Social Identity Is the Basis For Sports Group Leadershipmentioning
confidence: 99%
“…For example, in the context of the London 2012 Olympic Games, researchers [150] observed that successful leaders strove to mobilize team members by consistently articulating values in the media that communicated a positive, distinctive, and enduring sense of team identity. Relatedly, experimental research has shown that, because it enhances team members' social identification, the confidence leaders express in a team is a powerful determinant of basketball players' success in competition [90](see also [157]).…”
Section: Social Identity Is the Basis For Sports Group Leadershipmentioning
confidence: 99%
“…Accordingly, planning and organizing events that provide "us" the opportunity to live out the collective meaning in reality highlights the underpinning role of identity content in the achievement of the group's vision. Indeed, qualitative research that examined leadership surrounding the London 2012 Olympic Games documented the manner in which identity contents became the day-to-day fabric of group life and ultimately steered the group's direction (Slater, Barker, Coffee, & Jones, 2015). Thus, the communication of clear values that underpin the collective vision is crucial to the realization phase.…”
Section: Realizationmentioning
confidence: 99%